2017
DOI: 10.1186/s12872-017-0653-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-941 as a promising biomarker for acute coronary syndrome

Abstract: BackgroundCirculating miRNAs can function as biomarkers for diagnosis, treatment, and prevention of diseases. However, it is unclear whether miRNAs can be used as biomarkers for acute coronary syndrome (ACS). To this end, we applied gene chip technology to analyze miRNA expression in patients with stable angina (SA), non-ST elevation ACS (NSTE-ACS), and ST-segment elevation myocardial infarction (STEMI).MethodsWe enrolled patients with chest pain who underwent diagnostic coronary angiography, including five pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Our observation of lower expression levels of the above-mentioned angiogenesis-specific subset of miRNAs, which have been identified as crucial regulators of vascular biology and endothelial cell function, may indicate their potential angiogenesis-regulating role in premature gestation coupled with angiopoietic proteins imbalance in UCB found in this study. In this notion, the recent bioinformatics analyses have shown that miR-941, which appeared to be the most down-regulated microRNA in preterm newborns in our study, may be associated with metabolism, inflammation, cell proliferation, and other biological processes through regulation of components involved in insulin signaling, MAPK signaling cascade, and other pathways related pathophysiologically to coronary heart disease and atherosclerosis [82]. However, no research has yet been reported on the role of miR-941 in angiogenesis in course of preterm gestation.…”
Section: Discussionmentioning
confidence: 56%
“…Our observation of lower expression levels of the above-mentioned angiogenesis-specific subset of miRNAs, which have been identified as crucial regulators of vascular biology and endothelial cell function, may indicate their potential angiogenesis-regulating role in premature gestation coupled with angiopoietic proteins imbalance in UCB found in this study. In this notion, the recent bioinformatics analyses have shown that miR-941, which appeared to be the most down-regulated microRNA in preterm newborns in our study, may be associated with metabolism, inflammation, cell proliferation, and other biological processes through regulation of components involved in insulin signaling, MAPK signaling cascade, and other pathways related pathophysiologically to coronary heart disease and atherosclerosis [82]. However, no research has yet been reported on the role of miR-941 in angiogenesis in course of preterm gestation.…”
Section: Discussionmentioning
confidence: 56%
“…Functionally, miR-941 negatively regulated KDM6B (lysine (K)-specific demethylase 6B) to inhibit HCC cell epithelialmesenchymal transition (EMT) and cell migration/invasion [57]. Bai et al, reported that miR-941 levels are significantly higher in acute coronary syndrome patients than those in healthy controls [58].…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, miR-941 negatively regulated KDM6B (lysine (K)-specific demethylase 6B) to inhibit HCC cell epithelial-mesenchymal transition (EMT) and cell migration/invasion [57]. Bai et al, reported that miR-941 levels are significantly higher in acute coronary syndrome patients than those in healthy controls [58].…”
Section: Discussionmentioning
confidence: 99%